Hodnocení lymfatických uzlin v resekátech tlustého střeva s kolorektálním karcinomem - Dušek, M; Chlumská, A; Mukenšnabl, P; Zámečník, M (Rozhledy v chirurgii, 2013)
INTRODUCTION: Optimized staging of colorectal carcinoma (CRC) is essential for treatment planning and for estimating the prognosis of the disease. In addition to tumour size and the depth of bowel wall infiltration, the lymph node status is very important for the determination of the disease stage. For this reason, detection and assessment of the maximum number of lymph nodes is emphasized in the examination of resected segments of the large bowel. The number of lymph nodes (LNs) found in the segments resected depends on various circumstances. In our study, we focused on factors which could influence the number of pericolic LNs. MATERIAL AND METHODS: We examined two groups of CRC patients. The first group included 30 patients within the age range of 32-50 years (average: 47.5 years) and the second group consisted of 90 patients aged between 51 and 87 years (average: 68 years). The tumours were localized in various parts of the colon, predominantly in the descending colon and the sigmoid colon. Rectal tumour was present in 23 patients; 13 of them underwent preoperative chemoradiation therapy and 10 of them received no preoperative therapy. The length of the resected colon segments (radical intervention) ranged from 6 to 51 cm. The size of CRC ranged from 0.5 to 15 cm (average: 4.5 cm). The maximum tumour invasion depth reached into the subserosal tissue and pericolic adipose tissue. RESULTS: The number of LNs found in 120 resected colon segments ranged from 1 to 60 LNs per case. The number of LNs showed differences among the patients and also depended on the location of CRC within the large intestine. In the resected segments of the ceacum with CRC, the average number of LNs was 11.5, whereas it was only 7 in rectal CRC. The largest volume of pericolic adipose tissue was found in the caecum, whereas the smallest volume was seen on the rectal circumference. In CRC patients aged 50 years or younger, the number of LNs was from 2 to 60 (average: 17). In contrast, the number of LNs ranged from 1 to 46 (average: 11) in patients older than 50 years. In resected segments that were 6 to 12 cm long, the number of LNs ranged from 1 to 18 (average: 8). In resected segments that were 12 to 51 cm long, the number of LNs was from 1 to 60 (average: 13.8). In 13 cases of rectal CRC with preoperative chemoradiation therapy, small LNs of an average length of 1-3 mm predominated, and the number of LNs ranged between 1 and 13 (average: 5). The required number of 12 LNs was reached in 4 resected parts of the rectum (31%). CONCLUSION: The number of pericolic LNs found in the resected segments of the colon and the rectum with CRC depends on various factors. Besides individual differences, the number of LNs is influenced by the CRC location in the colon, the extent of the resected pericolic adipose tissue, the patients age and the length of the segment resected. In cases of rectal CRCs, it is also influenced by preoperative chemoradiation therapy.
Keywords: lymfatické uzliny; Colon, Sigmoid; Male; kolorektální nádory; Rectum; nádory rekta; Lymph Nodes; prognóza; Neoplasm Staging; Adult; Aged; dospělí; Rectal Neoplasms; mužské pohlaví; senioři; rektum; senioři nad 80 let; lidé; Carcinoma; ženské pohlaví; Humans; colon sigmoideum; karcinom; Aged, 80 and over; Colorectal Neoplasms; Prognosis; Female; lidé středního věku; staging nádorů; Middle Aged